COMMUNITY DEVELOPMENT GUIDELINES TO ENHANCE TOURISM MANAGEMENT POTENTIAL: A CASE STUDY OF OLD TOWN, PHUKET - Krudnak, Narisara; Charoenlak, Nipawan; Wongsa-ard, Nuanphun (Journal of MCU Nakhondhat, 2024)
This research article aims to 1) Study the potential of tourism management in the old town of Phuket Province and 2) Propose community development guidelines to enhance the potential for area-based tourism management. It is a qualitative study involving 12 key informants, consisting of 7 in-depth interviews and 5 focus group discussions, selected purposefully. The selection criteria included tourism management officials, stakeholders involved in tourism management, individuals with at least 3 years of tourism management experience, and those willing to provide information throughout the research. The data were analyzed using content analysis and validated with triangulation techniques. The research findings indicate that 1) The study on the potential for tourism management in the old town of Phuket reveals that the province possesses strong tourism management capabilities, with local community members actively establishing community enterprises aimed at enhancing the quality of life. 2) The study on community development guidelines to strengthen area-based tourism management suggests recommendations for achieving sustainability, including: Enhancing community capacity through education for community members, promoting community participation by establishing community enterprise groups, selecting community leaders, and holding regular meetings; Fostering sustainable tourism through awareness and consideration of environmental and community needs; Creating networks and collaborations by sharing knowledge with other provinces and adapting successful practices; and developing community leaders’ capacities through continuous learning and vision enhancement.